2019
DOI: 10.1080/08897077.2019.1573776
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Transition from Methadone to Buprenorphine using Naltrexone-Induced Withdrawal: A Case Report

Abstract: Background: Patients taking methadone for opioid use disorder may desire transition to buprenorphine for a number of reasons. However, the current recommended approach for this transition generally takes weeks to months as an outpatient, causing considerable discomfort to the patient and a heightened risk of relapse during the transition period. Case: We describe the case of a patient on methadone maintenance who was rapidly transitioned to buprenorphine because of her desire to not return to her methadone cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…This may be especially true for patients using fentanyl or other high potency synthetic opioid analogs, 7 which are increasingly prevalent contaminants in the North American drug supply 8 . The standard approach to starting buprenorphine in the hospital can be challenging due to patients’ severe illness, chronic pain, and anxiety around withdrawal 9–12,13 . There is, therefore, an urgent need for strategies to reduce barriers to in-hospital buprenorphine initiation to increase accessibility to this lifesaving medication.…”
mentioning
confidence: 99%
“…This may be especially true for patients using fentanyl or other high potency synthetic opioid analogs, 7 which are increasingly prevalent contaminants in the North American drug supply 8 . The standard approach to starting buprenorphine in the hospital can be challenging due to patients’ severe illness, chronic pain, and anxiety around withdrawal 9–12,13 . There is, therefore, an urgent need for strategies to reduce barriers to in-hospital buprenorphine initiation to increase accessibility to this lifesaving medication.…”
mentioning
confidence: 99%
“…First, subjects' baseline COWS score was 23, which is especially high. For reference, in a case of severe precipitated withdrawal, these authors reported a patient with a maximum COWS score of 17 (96). Authors also report that 0% of the subjects received any rescue medications, including opioid or benzodiazepine during the 5-day study period, which is both highly unusual and inconsistent with the standard of care (97).…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have been published recently demonstrating the efficacy of buprenorphine in acute opioid withdrawal, but only in cases of mild or moderate withdrawal, with COWS scores at buprenorphine induction ranging from 4 to 17 [ 2 4 , 8 ]. We have presented a unique case demonstrating that buprenorphine is efficacious for significant reduction of withdrawal symptoms in moderately severe acute precipitated opioid withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of naltrexone with measurable levels of opioids in the body can precipitate acute withdrawal, but withdrawal symptoms often appear more severe than usual [7]. One recent study found that elective naltrexone-induced withdrawal could be treated with buprenorphine in order to avoid methadone tapering and hasten treatment [8]. To the best of the authors' knowledge, this is the first case of an accidental oral naltrexone ingestion after intravenous (IV) heroin use that was successfully treated by oral buprenorphine.…”
Section: Introductionmentioning
confidence: 89%